Rethinking social media and extremism - Leitch, Shirley, 1960- (Australia and the World., 2022)
Terrorism, global pandemics, climate change, wars and all the major threats of our age have been targets of online extremism. The same social media occupying the heartland of our social world leaves us vulnerable to cybercrime, electoral fraud and the 'fake news' fuelling the rise of far-right violence and hate speech. In the face of widespread calls for action, governments struggle to reform legal and regulatory frameworks designed for an analogue age. And what of our rights as citizens? As politicians and lawyers run to catch up to the future as it disappears over the horizon, who guarantees our right to free speech, to free and fair elections, to play video games, to surf the Net, to believe 'fake news'? Rethinking Social Media and Extremism offers a broad range of perspectives on violent extremism online and how to stop it. As one major crisis follows another and a global pandemic accelerates our turn to digital technologies, attending to the issues raised in this book becomes ever more urgent. -- Publisher.